PENDEKATAN TEKNOLOGIS DALAM PENINGKATAN KUALITAS DAN MUTU PENDIDIKAN TINGGI ISLAM MELALUI REKAYASA INSTITUSI - Supandi, Supandi (Universitas Islam Madura, 2016)
Improving the quality of education in various educational institutions already selaknya done, both the concept and sector inplementatifnya, therefore, engineering education is an alternative that needs to be done by all parties concerned with the provision of education, particularly in institutions educational institutions in Indonesia, both in the form the launching of the school / madrasah and even featured colleges, which are projected to develop the potential and creativity of talented children or special ability, and so forth. Therefore, they are a valuable asset for the nation's future. While the form of the development can be done through three ways, namely (1) through the existing school and then coupled with enrichment; (2) through the use of educational media; and (3) through the school / special classes as much developed now. While the flagship school in general management includes three things: input, process and output. All of them were selected and well managed with management planned and implemented seriously. While relation to Islamic education, school / madrasah featured aimed at integrating the science of religion and general knowledge, in order to have the intellectual output, high creativity and leadership, as well as pay attention to the moral and spiritual aspects. While management is implemented in the schools featured a school-based management designed and implemented optimally.